2008
DOI: 10.1213/01.ane.0000297297.79822.00
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Administration of Ketorolac, Morphine, and Ropivacaine Combined with Intraarticular Patient-Controlled Regional Analgesia for Pain Relief After Shoulder Surgery: A Randomized, Double-Blind Study

Abstract: A combination of intraarticular ropivacaine, morphine, and ketorolac followed by intermittent injections of ropivacaine as needed provided better pain relief, less morphine consumption, and improved patient satisfaction compared with the control group. The group that received IV ketorolac consumed less morphine and was more satisfied with treatment than patients in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…A far-superior randomized, double-masked investigation evaluated the efficacy of patient-controlled intraarticular analgesia following Bankart shoulder surgery [8•]. Fifty-one patients were randomized into one of two infusions: ropivacaine/morphine/ketorolac or isotonic saline.…”
Section: Single-injection Peripheral Nerve Blocksmentioning
confidence: 99%
“…A far-superior randomized, double-masked investigation evaluated the efficacy of patient-controlled intraarticular analgesia following Bankart shoulder surgery [8•]. Fifty-one patients were randomized into one of two infusions: ropivacaine/morphine/ketorolac or isotonic saline.…”
Section: Single-injection Peripheral Nerve Blocksmentioning
confidence: 99%
“…Bektas that assessed in his study morphine and intravenous paracetamol in patients with renal colic, finally, suggested the latter as an effective and harmless treatment for renal colic patients admitted to the emergency department [20]. Axelsson that examined a composition of ropivacaine, morphine, and ketorolac in reducing patients pain after shoulder surgery, showed that subjects who had received more ketorolac than morphine were more satisfied [21]. Although both kinds of drugs used in current study were titratable, but as previously expressed in the section "intervention" there was no need for titration in present work.…”
Section: Discussionmentioning
confidence: 99%
“…Improved postoperative pain control using the ISB method is linked to an earlier initiation of rehabilitation, as evident in other studies [ 18 ]. IA has been popular among surgeons because it is perceived as a simple and effective technique associated with improved analgesia, the reduced use of analgesics, and improved patients' satisfaction [ 3 , 19 , 20 ]. Savoie et al demonstrated improved analgesia and reduced analgesic requirements with a continuous IA of 0.25% bupivacaine (2 ml/h for 48 h) in patients undergoing subacromial decompression under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported that, IA was an effective alternative to ISB [ 3 , 19 ]. However, the results of the current study were identical to those of other studies, finding that ISB provided better pain control than IA [ 8 ].…”
Section: Discussionmentioning
confidence: 99%